Optimal Timing of Surgical Decompression for Acute Traumatic Central Cord Syndrome - Anderson, Karen K.; Tetreault, Lindsay; Shamji, Mohammed F.; Singh, Anoushka; Vukas, Rachel R.; Harrop, James S.; Fehlings, Michael G.; Vaccaro, Alexander R.; Hilibrand, Alan S.; Arnold, Paul M. (Neurosurgery, 2015)
Abstract BACKGROUND: Traumatic central cord syndrome (TCCS) is an incomplete spinal cord injury defined by greater weakness in upper versus lower extremities, variable sensory loss, and variable bladder, bowel, and sexual dysfunction. The optimal timing of surgery for TCCS remains controversial. OBJECTIVE: To determine whether timing of surgery for TCCS predicts neurological outcomes, length of stay, and complications. METHODS: Five databases were searched through March 2015. Articles were appraised independently by 2 reviewers, and the evidence synthesized according to Grading of Recommendation Assessment, Development and Evaluation principles. RESULTS: Nine studies (3 prognostic, 5 therapeutic, 1 both) satisfied inclusion criteria. Low level evidence suggests that patients operated on <24 hours after injury exhibit significantly greater improvements in postoperative American Spinal Injury Association motor scores and the functional independence measure at 1 year than those operated on >24 hours after injury. Moderate evidence suggests that patients operated on <2 weeks after injury have a higher postoperative Japanese Orthopaedic Association score and recovery rate than those operated on >2 weeks after injury. There is insufficient evidence that lengths of hospital or intensive care unit stay differ between patients who undergo early versus delayed surgery. Furthermore, there is insufficient evidence that timing between injury and surgery predicts mortality rates or serious or minor adverse events. CONCLUSION: Surgery for TCCS <24 hours after injury appears safe and effective. Although there is insufficient evidence to provide a clear recommendation for early surgery (<24 hours), it is preferable to operate during the first hospital admission and <2 weeks after injury.